(untitled) (The Agriculturists, 2014)
An experiment was conducted with three popular potato varieties viz. Cardinal, Diamant and Asterix to create somaclonal variation in potato. The chemical mutagens viz. Ethyl methane sulphonate (EMS), Methyl methane sulphonate (MMS), 5-Bromo Uracil (BU) and 2,4-D were used in three different concentration (1.0, 2.0 and 4.0 mg/L). Among them only 2,4-D regenerated callus in potato. Higher concentration (4.0 mg/L) of 2,4-D showed variant type of callus, which regenerated abnormal plantlet and some of the plantlets died within 45 days after inoculation. The higher concentration (4.0 mg/L) of EMS, MMS and BU showed huge abnormality on in vitro regeneration in all three varieties of potato. Thin stem, deformed shoot development and very less leaf formation were observed in 2.0 mg/L and 4.0 mg/L of EMS, MMS and BU. Due to toxic effect some of the plantlets died. The mutagen treated variants were acclimatized in plastic tray and subsequently in the field condition. It was noticed that, only 37.16% plants survived in natural field condition. Morphological characterization and yield potentiality of all somaclones were studied. It revealed that only one variants viz. SVP-53 showed higher yield as compared with two check varieties. The first generation mini tubers were kept for further research. DOI: http://dx.doi.org/10.3329/agric.v12i1.19572 The Agriculturists 2014; 12(1) 15-25